Historical Flow of Migrant Muslim Communities in Korea: A Perspective on Discontinuity - Soojeong Yi; Junga Yang (International Journal of Korean History)
This study explores the history of Islam in Korea, focusing on discontinuity as a defining characteristic. Migrant Muslim communities, from the Koryŏ and Chosŏn periods to modern times, arrived in waves, disconnected from previous generations. This study classifies the history of Islam in Korea into four periods using primary sources, including historical texts from the Koryŏ and Chosŏn periods and records from the Japanese colonial era. It highlights the transient nature of Muslim communities in Korea, driven by shifts in international relations and the policies of ruling elites. The four periods－Shilla period (possibilities of early Muslim contact), Koryŏ and Chosŏn periods (Huihui Muslims), Japanese colonial period and Korean War (Tatar and Turkic Muslims), and post-1990 (Muslim community diversification)－illustrate how migrant Muslims have historically been brought to Korea by external forces and left with regime changes. The absence of continuity in transmitting Islamic traditions and practices between these periods reflects the complex relationship between Korea and Islam. The study concludes by addressing the challenges of integrating migrant Muslim communities into contemporary South Korean society. It proposes that a deeper understanding of this historical relationship is essential for fostering coexistence in the future.